A Siloxene/Ecoflex Nanocomposite‐Based Triboelectric Nanogenerator with Enhanced Charge Retention by MoS2/LIG for Self‐Powered Touchless Sensor Applications (Adv. Funct. Mater. 27/2022). (4th July 2022) - Shrestha, Kumar; Sharma, Sudeep; Pradhan, Gagan Bahadur; Bhatta, Trilochan; Maharjan, Pukar; Rana, SM Sohel; Lee, Sanghyun; Seonu, Sookyeong; Shin, Youngdo; Park, Jae Y.
Abstract : Triboelectric Nanogenerators In article number 2113005, Jae Y. Park and co‐workers develop a Siloxene/Ecoflex based contactless triboelectric nanogenerator (TENG) to reduce the possible contact situations and improve the robustness and functionality of the TENG. The MoS2 /LIG‐based charge trapping interlayer exhibits excellent charge trapping property and aids in the realization of the TENG as a self‐powered sensor for touchless interactions.